Blending Quadruplexes and Bordeaux: A Grand Cru!. Issue 3 (17th March 2016) - Yatsunyk, Liliya A.; Monchaud, David; Sen, Dipankar
Abstract : The Fifth International Meeting on Quadruplex Nucleic Acids took place in Bordeaux, France. Over the course of three intense days in May 2015, the quadruplex community had an opportunity to share exciting developments in the field, especially key insights into emerging biological roles that these structures, considered for decades to be nothing more but in vitro curiosity, are playing. Abstract : Every two years those working in the quadruplex field gather for an intense meeting to discuss what is new and noteworthy in their field. One of these gatherings took place in 2015 and Yatsunyk et al. now report on the Fifth International Meeting on Quadruplex Nucleic Acids.